Comparative Study of University Mascots in Indonesia: Analysis of Visual Identity and Audience Acceptance - Fitria, Viny; Wardaya, Marina (ULTIMART Jurnal Komunikasi Visual, 2025)
This study investigates Indonesian university mascots as instruments of visual identity and branding through a descriptive-comparative qualitative methodology employing Roland Barthes' semiotic analysis. Methodological study conduct used Roland Barthes semiotic framework to examine how visual element represent institutional ideology. The analysis included four mascots: YUCCA (Ciputra University), ROGA (Bandung Institute of Technology), BRONE (Brawijaya University), and CAKRA (Malang State University). Data collection encompassed visual documentation, institutional philosophy analyses, social media monitoring, and surveys involving 50 participants from East Java. The results show that good mascots need three things: a unique look, a philosophy that fits with the values of the institution, and regular activity on social media. Mascots that include elements of local culture, like CAKRA and ROGA, are more real than those that are based on Western culture, like YUCCA. The research demonstrates a dialectical relationship between academic credibility and popular aesthetics, affirming that mascots serve as semiotic agents that construct institutional myths rather than mere decorative components. Visual design alone is not enough, it needs to be strategically activated. This is shown by BRONE's low engagement even though the design was clear. According to the survey, 86.5% of respondents are very familiar with mascots through social media. They like simple shapes, unique personalities, and the ability to tell stories. Recommendations encompass participatory design methodologies, cultural integration frameworks, and ongoing digital engagement initiatives. Subsequent research ought to investigate longitudinal studies, regional comparisons, and quantitative impact evaluations concerning brand equity.